PENGARUH PEMBERDAYAAN MASYARAKAT TERHADAP COMMUNITY BASED TOURISM DAN KESEJAHTERAAN MASYARAKAT PADA CEKING RICE TERRACE, TEGALLALANG - Suryawan, Adi; Utama, Made Suyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.08.TAHUN.2021DO - 10.24843/EEB.2021.v10.i08.p03, 2021)
This study aims to determine the effect of community empowerment on community based tourism (CBT) and community welfare at the Ceking Rice Terrace tourist attraction, Tegallalang, Gianyar. The sample of this study were 88 people through simple random sampling. The data collection method used was questionnaire distribution. The data analysis technique used is the Structural Equation Model (SEM) with the Partial Least Square (PLS) approach. The results showed that community empowerment had a positive effect on CBT and community welfare, community empowerment and CBT had a positive effect on community welfare, and CBT was able to positively mediate the effect of empowerment on community welfare. Community empowerment should be further improved because there are still many people who do not participate in the development of tourist objects, especially Ceking Rice Terrace, which causes economic disparities in Tegallalang Village and there are still people who do not have a job, or in other words, the welfare of the community has not yet been realized.